Volume 1: Symposia, Parts A, B and C 2009
DOI: 10.1115/fedsm2009-78545
|View full text |Cite
|
Sign up to set email alerts
|

CFD Simulation of Temperature Distribution in a Room With Various Under Floor Heating System Models

Abstract: Limited resources of energy are the major challenges of the industrial and developing communities (countries), so engineers are increasingly encouraged for new ideas of producing energy from the today’s natural resources such as sun light and wind instead of fossil resources. In this study, flow of air in a 3D flow field surrounded by several walls and windows (a room) as laminar, and flow of water in a 3D flow filed (a pipe) placed on the bottom of the room as turbulent in an incompressible flow condition is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Most of the numerical methods applied for this study are nearly similar to that of several other studies [9][10][11][12][13]. However, the study of changes in the pressure inlet on the temperature distribution and comparing different piping arrangements are different from others.…”
Section: Comparison With Other Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Most of the numerical methods applied for this study are nearly similar to that of several other studies [9][10][11][12][13]. However, the study of changes in the pressure inlet on the temperature distribution and comparing different piping arrangements are different from others.…”
Section: Comparison With Other Studiesmentioning
confidence: 98%
“…However, there are still uncertainty or limitation reference regarding the heating pad for flexitank application. The most of previous research was conducted on floor heating pads, with applications similar to heating pads for flexitank [7][8][9][10][11][12][13]. One of the solutions to minimize the time taken to completely liquidize for discharging process is identify the finest arrangement of heating pad.…”
Section: Introductionmentioning
confidence: 99%
“…Along with a calculator programme to account temperature field, she found that floor heating system was propitious to intermittent regulate and control operation. Furthermore, Izadi MJ [11] carried out CFD simulations for different floor heating models. Literature [12] analysed the temperature distribution when the heating floor adopted dissimilar materials.…”
Section: Introductionmentioning
confidence: 99%
“…The variables are two models of pipes arrangements, three types of pipes, and several pipe diameters. As a result, in an underfloor heating system, the reciprocating model using the PAP pipe type of 16 mm pipe diameter are the best parameter values for a good comfortable room temperatures [12]. Chen Jiao Liao (2011) proposed optimized design of hot air pipe in greenhouse based on CFD tech- tuned and used to control the internal temperature in the greenhouse.…”
Section: Introductionmentioning
confidence: 99%